Assessing the population health impact of market interventions to improve access to antiretroviral treatment (2012)
Develops a framework to structure ex ante and ex post assessment of the population health impact of market interventions, which is transmitted through effects in markets and health systems. Discusses methods for ex post assessment and analyses assessment issues (unintended intervention effects, interaction effects between different interventions, and assessment impartiality and cost. Offers seven recommendations for ex ante and ex post assessment.
Keywords: MEDICAL CARE